Adaptive vertical-deformation field estimation and current tectonic deformation significance analysis in Shanxi rift valley - Liu, Ruichun; Zhang, Jin; Guo, Wenfeng; Chen, Hui (Frontiers in Earth Science, 2023)
The Shanxi rift valley is a continental rift system that is characterized by mantle uplift, crustal thinning, and tectonic deformation. A continuous, vertical crustal-deformation field can elucidate the constraints for understanding the mechanisms currently driving the deformation of the rift. Accordingly, we acquired and processed data from 250 continuous and mobile GPS stations located in the Shanxi rift valley and its surrounding region. Accounting for the influence of fault activity, we established the vertical crustal-deformation field of the Shanxi rift valley as a continuous function of space, using an adaptive least-squares collocation method. The main research findings are stated as follows: (1) the adaptive least-squares model yielded a reliable interpolation prediction results with adequate robustness, even for relatively sparse actual observation data. (2) The current general deformation pattern of the Shanxi rift valley exhibits an uplift of the mountainous regions on both sides and subsidence of the central basin. The average uplift rate of the mountain area is 2–3 mm/a, and the subsidence rate of the basin is not uniform and is positively correlated with the spatial distribution of the Cenozoic sediment thickness. However, in certain areas, a high subsidence rate of 10–30 mm/a is associated with human activities such as groundwater exploitation. (3) In summary, the current vertical crustal deformation occurring in the Shanxi rift valley correlates with the pattern over a time scale of millions of years. Overall, it is controlled by regional geological structure pattern, and is influenced by nonstructural factors in the shallow crust, exhibiting both complex and orderly characteristics in its spatial distribution.